FINANCIAL MANAGEMENT IN SOUTH AFRICAN PUBLIC SCHOOLS: PERSPECTIVES FROM PRINCIPALS - Schlebusch, Gawie; Mokhampanyane, Matsolo (Indonesian Journal of Educational Development (IJED), 2024)
Compliance to the law and policies that govern public schools in South Africa is fundamental in ensuring effective and efficient use of school funds. Compliance can mitigate the role confusion between the respective duties of the school principal as the manager of the school and the School Governing Body (SGB). This aim of the study was to identify the gap on compliance from the principals’ point of view. The qualitative design with phenomenological approach was used, and data was collected by means of semi-structured interviews with purposefully sampled principals. The literature and findings reveal that many SGB chairpersons are still profoundly reliant on principals regarding financial decisions and management at schools. This indicates the perpetuation of role confusion where school principals regard themselves as accountable for school funds. Even though financial management challenges in public schools have been researched before, the study found that such challenges still occur and hamper effective financial management by both the principals and SGBs.